2021
DOI: 10.1071/py20150
|View full text |Cite
|
Sign up to set email alerts
|

Using the National Mental Health Service Planning Framework to support an integrated approach to regional mental health planning in Queensland, Australia

Abstract: Regional integrated service planning has been identified as a key priority for improving the mental health system in Australia. The National Mental Health Service Planning Framework (NMHSPF) is an integrated planning tool that estimates the resources required to deliver the optimal mix of mental health services to a population. In 2016, Queensland Health commissioned a trial application of the NMHSPF for joint mental health planning between a Primary Health Network (PHN) and the corresponding state Hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…This problem has been identified as a major source of systematic bias in international health service research [ 49 ]. As an example, the “National Mental Health Service Planning Framework” adopted by the Department of Health in Australia has shown terminological problems when compared to DESDE in the description of “psychosocial/rehabilitation” services [ 50 ] and in its practical use to map the availability of local care provided by the NGO sector [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This problem has been identified as a major source of systematic bias in international health service research [ 49 ]. As an example, the “National Mental Health Service Planning Framework” adopted by the Department of Health in Australia has shown terminological problems when compared to DESDE in the description of “psychosocial/rehabilitation” services [ 50 ] and in its practical use to map the availability of local care provided by the NGO sector [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, an independent assessment of the optimal service evaluation system should be conducted comparing the DESDE-LTC system used in this study, which has demonstrated its usability in analysis of system evolution, with the NMHSPF. The only published paper citing use of the NMHSPF for regional mapping was unable to provide a description of the NGO sector in the mapped region (Wright et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…. in the absence of standardised reporting and detailed information on the number of sessions and specific types of services being provided' (Wright et al, 2021). Yet, mapping the landscape of service provision before and after a reform is vital to understand the effects of major disruption and provider response (Gash et al, n.d.) and to assess the impact on implementation of a plan or strategy (Fernandez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Australian National Mental Health Services Planning Framework (NMHSPF) is one example of an integrated planning tool that estimates the resources required to deliver the optimal mix of mental health services to a population [ 50 ]. In Australia, it is critical that the NMHSPF, which currently does not plan for suicide and crisis, let alone the implications of recent paradigm shifts, is revised to take account of, and recognise, suicide and crisis, as well as the shift in paradigm impacting service activity, and increases in presentations.…”
Section: The Paradox At a System Planning And Strategy Levelmentioning
confidence: 99%